2014
DOI: 10.1002/pat.3332
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an antimicrobial poly(lactic acid) film prepared with poly(ε‐caprolactone) and thymol for active packaging

Abstract: Antimicrobial active films based on poly(lactic acid) (PLA) were prepared with poly(ε‐caprolactone) (PCL) and thymol (0, 3, 6, 9, and 12 wt%) by solvent casting methods. The films were characterized by thermal, structural, mechanical, gas barrier, and antimicrobial properties. Scanning electron microscopy analysis revealed that the surface of film became rougher with certain porosity when thymol was incorporated into the PLA/PCL blends. Thymol acted as plasticizers, which reduce the intermolecular forces of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 37 publications
(65 reference statements)
6
38
0
Order By: Relevance
“…The incorporation of thymol especially at 15 and 20 wt.% significantly reduced crystallinity of the antifungal films. This was consistent with the study of Wu et al (2014) [6] who reported that as the amount of thymol increased, the T g value decreased from 46.7°C of PLA/PCL to 41.3°C of PLA/PCL/T12 composite film. A decrease in T g value was a good indication of the extent of the plasticizing effect provided by thymol.…”
Section: Smae 2016supporting
confidence: 92%
See 3 more Smart Citations
“…The incorporation of thymol especially at 15 and 20 wt.% significantly reduced crystallinity of the antifungal films. This was consistent with the study of Wu et al (2014) [6] who reported that as the amount of thymol increased, the T g value decreased from 46.7°C of PLA/PCL to 41.3°C of PLA/PCL/T12 composite film. A decrease in T g value was a good indication of the extent of the plasticizing effect provided by thymol.…”
Section: Smae 2016supporting
confidence: 92%
“…This was due to high plasticization effect of 20% thymol and 15% R-(-)-carvone in decreased brittleness and increased flexibility of the antifungal films [17]. As reported by Wu et al (2014) [6], thymol acted as plasticizer, reducing the intermolecular forces of polymer chains, thus improving the flexibility and extensibility of the films. Moreover, the presence of thymol decreased the crystallinity of PLA phase.…”
Section: Smae 2016mentioning
confidence: 71%
See 2 more Smart Citations
“…carvacrol and thymol. [15] Essential oils are natural substances categorized as GRAS (generally recognized as safe) by the Food and Drug Administration (FDA), and most of them are derived from plants. [16] They have shown substantial antibacterial and antifungal properties achieved both in direct contact and in vapor phase.…”
Section: Introductionmentioning
confidence: 99%